Core I97L mutation in conjunction with P79Q is associated with persistent low HBV DNA and HBs antigen clearance in patients with chronic hepatitis B. (June 2017) - Honda, T.; Ishigami, M.; Ishizu, Y.; Kuzuya, T.; Hayashi, K.; Ishikawa, T.; Murakami, Y.; Iwadate, M.; Umeyama, H.; Toyoda, H.; Kumada, T.; Katano, Y.; et al.
Abstract: Objectives: When considering treatment for chronic hepatitis B (CHB), it is important to discriminate between patients with persistent low HBV DNA and patients with active hepatitis, who may proceed to cirrhosis. In this study, we sought to identify mutations in patients expected to have persistent low HBV DNA and ultimately exhibit clearance of hepatitis B surface antigen (HBsAg). Methods: Serum samples were obtained from 33 CHB genotype C patients, divided based on HBV DNA and alanine aminotransferase (ALT) levels following observation for >2 years: Group A ( n  = 10), transient HBV DNA ≥5.0 log copies/mL and ALT ≥120 IU/L; Group B ( n  = 11), persistent HBV DNA <5.0 and ALT <60; and Group C ( n  = 12), persistent HBV DNA <4.0 and ALT <30. Full-length HBV sequences were compared among groups. Subsequently, 82 patients with CHB were evaluated for the I97L mutation and the additional mutation P79Q. We compared cumulative incidences of persistent low HBV DNA and HBsAg clearance in patients with or without I97L and P79Q by the Kaplan–Meier method. Results: Incidence of Core mutation I97L differed significantly among groups: A, 30% (3/10); B, 36.4% (4/11); C, 83.3% (10/12) (p = 0.021). Cumulative incidences of persistent low HBV DNA and HBsAg clearance were significantly higher in patients with I97L than in those with wild-type I97 (p = 0.003 and p = 0.016, respectively), and even higher in those with P79Q. Conclusions: In patients with CHB, measurement of I97L and additional mutation P79Q would be useful for predicting persistent low HBV DNA, normal ALT, and HBsAg clearance.